Pengaruh Return On Asset Dan Debt To Equity Ratio Terhadap Price To Book Value Pada PT Hanjaya Mandala Sampoerna Tbk - Musanah, Ayu; Nurhayati, Nurhayati; Huda, Nurul (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the effect of Return on Asset (ROA) and Debt to Equity Ratio (DER) on Price to Book Value (PBV) at PT Hanjaya Mandala Sampoerna Tbk during the 2013–2023 period. The research applies a quantitative approach with an associative method. Secondary data were obtained from the Indonesia Stock Exchange in the form of annual financial reports, selected using purposive sampling. Data analysis was conducted using multiple linear regression, including classical assumption tests, t-test, F-test, and the coefficient of determination. The results show that partially ROA has a significant positive effect on PBV, while DER does not significantly affect PBV. However, simultaneously ROA and DER significantly influence PBV, with a determination coefficient of 88.6%. These findings indicate that profitability is a more dominant factor in determining firm value compared to capital structure. This study highlights the importance of asset management efficiency as the main strategy to enhance firm value, while DER should still be managed to minimize potential financial risks.